2017
DOI: 10.1002/hbm.23879
|View full text |Cite
|
Sign up to set email alerts
|

Functional dysconnectivity of the limbic loop of frontostriatal circuits in first‐episode, treatment‐naive schizophrenia

Abstract: Frontostriatal circuits dysfunction has been implicated in the etiology and psychopathology of patients with schizophrenia (SZ). However, few studies have investigated SZ-related functional connectivity (FC) alterations in discrete frontostriatal circuits and their relationship with pathopsychology in first-episode schizophrenia (FESZ). The goal of this study was to identify dysfunctions in discrete frontostriatal circuits that are associated with key features of FESZ. To this end, a case-control, cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 101 publications
5
19
0
Order By: Relevance
“…102 The putamen also has widespread connections with the frontal cortex, involved in motor sequence performance and habitual instrumental behaviour; executive function and goal-directed behaviour; emotion processing; and reinforcement learning. 103 In our metaanalysis, the increased cluster of putamen in patients with first-episode schizophrenia did not appear in patients with chronic schizophrenia; we speculate that increased ALFF in the putamen plays an important compensatory mechanism for maintaining normal cognitive performance in the early stages of schizophrenia. Interestingly, our study observed an inconsistent activation in the VN regions (occipital gyrus, including BA 17,18 and 19).…”
Section: Alff Alterations In Patients With First-episode Schizophreniamentioning
confidence: 53%
“…102 The putamen also has widespread connections with the frontal cortex, involved in motor sequence performance and habitual instrumental behaviour; executive function and goal-directed behaviour; emotion processing; and reinforcement learning. 103 In our metaanalysis, the increased cluster of putamen in patients with first-episode schizophrenia did not appear in patients with chronic schizophrenia; we speculate that increased ALFF in the putamen plays an important compensatory mechanism for maintaining normal cognitive performance in the early stages of schizophrenia. Interestingly, our study observed an inconsistent activation in the VN regions (occipital gyrus, including BA 17,18 and 19).…”
Section: Alff Alterations In Patients With First-episode Schizophreniamentioning
confidence: 53%
“…Most prominently, the anterior cingulate cortex (ACC) encodes reward predictions and reward prediction errors ( Bissonette and Roesch, 2016 ), receives input not only from the VTA ( Decot et al, 2017 ) but also the LC ( Fillinger et al, 2017 ), and projects to the associative and—to a lesser extent—the ventral striatum ( Fillinger et al, 2018 ) ( Figure 2 ). The latter (ACC→NAc) connection is functionally reduced in first-episode schizophrenia ( Lin et al, 2018 ). The ACC also projects to further key structures of the extended vSub/VTA circuit, such as the amygdala and the vHC ( Figure 2 )—these connections are crucial for attribution of the appropriate levels of significance during associative learning ( Bian et al, 2019 ; Ortiz et al, 2019 ).…”
Section: Limitations and Challenges Of Harnessing The Hippocampus→nacmentioning
confidence: 99%
“…However, several indications point to the caudate nucleus (CN) as being a primary node of dysfunction in SCH (Li et al, 2018). For instance, functional hypo-connectivity was found between the frontal cerebral cortex and the CN in treatmentnaïve first-episode patients with SCH (Lin et al, 2018). Furthermore, reduced structural connectivity was observed between the frontal cerebral cortex and the CN in SCH (Levitt et al, 2017).…”
Section: Introductionmentioning
confidence: 99%